Transcriptomic insight into the underlying mechanism of induced molting on reproductive remodeling, performance and egg quality in laying hen - Pengyun Ma; Fuguang Xue; Jilan Chen; Xiaoke Zhang; Xinying Xu; Zhong Ma; Hao Zhang; Yan Wu; Ling Li; Yuanqi Qu; Yunlei Li (Poultry Science)
This study aimed to clarify the reproductive remodeling mechanism in enhancing production performance and egg quality during the fasting-induced molting process of laying hens. A total of two-hundred and forty 380-days-old Jingfen No. 6 laying hens, with an average laying rate of 78% were divided into four replicates, with 60 hens in each replicate to receive a four-stage molt induction experiment. The stages encompassed the pre-molt stage (T1), the molt stage (T2), the recovery stage (T3), and the second peak-laying stage (T4). The egg-laying rate and egg quality were recorded during all stages, and sample collection (serum, magnum of oviduct, ovary) was conducted at the end of each stage. The length and index of oviduct, the number of hierarchical follicles, and serum reproductive hormone levels were further measured, followed by the transcriptomic sequencing process on the magnum of the oviduct and ovarian tissues at each stage. Results showed that the fasting treatment induced atrophy of the oviducts, the disappearance of large yellow follicles in the ovaries, and the decrease in serum reproductive hormone levels compared to the pre-molt stage. Transcriptomic analysis revealed that differentially expressed genes were notably enriched in cytokine-cytokine receptor interactions, cell adhesion molecules, and the arachidonic acid metabolism signaling pathway during the remodeling phases of oviduct and ovary tissues. Key candidate genes such as BMPR1B, NEGR1, VTN, and CHAD emerged as pivotal in influencing reproductive function remodeling in molt-treated chickens. Additionally, genes associated with steroid biosynthesis showed significant up-regulation in the ovaries of molted hens, correlating positively with egg-laying rates. Furthermore, genes related to collagen and laminin displayed significant positive associations with Albumen height and Haugh unit values. The results indicate that fasting interventions might modulate the remodeling of reproductive functions in laying hens by altering cytokine-cytokine receptor interactions, cell adhesion molecules, and arachidonic acid metabolic pathways. Enhanced ovarian steroid biosynthesis and up-regulation of gene expression, including oviductal collagens post-molting, are crucial for enhancing laying rates and egg quality. These findings could offer novel thinking for refining molting protocols.